Ureteroscopy in pregnant women with complicated colic pain: Is there any risk of premature labor? - ŞENER, TARIK EMRE; TANIDIR, YILÖREN (PAGEPRESS PUBL, 2017)
Objective: Clinical presentation of ureteral stones during pregnancy is generally with renal colic pain. The aim of this study is to present our experience in the management of renal colic during pregnancy in emergency settings. Materials and methods: 208 pregnant patients who presented to emergency department with renal colic pain and underwent ureteroscopy (URS) due to failed conservative therapy were enrolled in the study. Urinary tract stones were diagnosed either with ultrasound (US) examination or during URS. Laser lithotripsy and double J (DJ) stent placement were routinely done in all patients with ureteral stones. The incidence of infective complications and premature uterine contractions (PUC) due to URS were compared. Results: No stone was identified in 36.1% (n = 75) of patients with using US and diagnostic URS. Of the remaining 133 patients, 30 (22.6%) had no stone at US but stones were diagnosed during diagnostic URS. The type of anesthesia had no significant effect on PUC. An increased risk of sepsis and PUC was found in patients with fever at the initial presentation. Interestingly, PUC was more frequent in patients with lower serum magnesium levels. There was a significant correlation with time delay until the intervention and the risk of urosepsis and PUC, individually. Conclusions: Ureteroscopy is a safe option for evaluation of pregnant patients with unresolved renal colic. According to the current findings, timing of the operation is the most important factor affecting the septic risks and abortion threat. Surgical intervention with URS must be planned as soon as possible.
Keywords: Pregnancy; Urinary calculi; Renal colic; URETERAL CALCULI; URINARY CALCULI; PRETERM BIRTH; MANAGEMENT; UROLITHIASIS; OBSTRUCTION; DEXAMETHASONE; BETAMETHASONE; GUIDELINES